SYNTHESIS AND ANALYSIS OF REED-SOLOMON CODES IN ISOMORPHIC SPACE OF IMAGES - A.J. Beletsky; А.А. Beletsky; O.I. Volyvach; M.A. Yakymchuk (Ìнформаційні технології в освіті, 2013)
A training variant of Reed-Solomon codes, which greatly simplifies the process of synthesis of codewords and detection-fixes for corrupted data files. The algorithm is based on the transfer of variables and operations, in which the synthesis and analysis of codes from the original space into isomorphic space of image. As a result, the proposed replacement of data space computational process is reduced to the basic operations in a simple and modular Galois field arithmetic on integer operands, easily implemented by means of computer technology.